(untitled) (Jurnal Bahasa, 2014)
Impressionistic studies by local linguists to determine the difference in vowel production based on gender have not yet been conclusive. Previous studies of Malay vowels are more on the general tone (description of vowel patterns without specifying the differences between men and women). This phonetics research utilizes the spectrographic method to study the acoustic traits of Malay vowels according to gender. A total of five male and five female native speakers were chosen as subjects. Some sample utterances were recorded and then analysed spectrographically using the software, Praat. The research was focused on the fundamental frequency (F0). F0 is the acoustic signal indicating the pitch level of the sound wave, and also the lowest frequency or first harmonic of a periodic waveform. The findings of this study emphasize that there is a significant difference of the F0 between the production of vowel sounds of males and females. This study is expected to clarify the acoustic features of Malay vowels. Keywords: phonetics, acoustics, fundamental frequency, gender